Efficacy of Margetuximab vs Trastuzumab in Patients With Pretreated ERBB2-Positive Advanced Breast Cancer A Phase 3 Randomized Clinical Trial - Rugo, Hope S.; Im, Seock-Ah; Cardoso, Fatima; Cortes, Javier; Curigliano, Giuseppe; Musolino, Antonino; Pegram, Mark D.; Wright, Gail S.; Saura, Cristina; Escriva-De-Romani, Santiago; De Laurentiis, Michelino; Levy, Christelle; et al. (JAMA Oncology, 2021)
IMPORTANCE ERRB2 (formerly HER2)-positive advanced breast cancer (ABC) remains typically incurable with optimal treatment undefined in later lines of therapy. The chimeric antibody margetuximab shares ERBB2 specificity with trastuzumab but incorporates an engineered Fc region to increase immune activation.
CRIS-Team WoS Importer:2021-01-29